2003
DOI: 10.1002/mats.200390013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Azobenzene Liquid Crystalline Polymers

Abstract: This paper presents a computational conformational study undertaken to explain the liquid crystalline behaviour of some polyethers with high transition temperature values. The study is based on a very significant number of polymers and copolymers (over 1 400) that were simulated to investigate the correlation between the chain geometry, flexibility, inter‐chain interactions and orientational properties over liquid crystalline behaviour. Some of the simulated polymers were synthesised from 3,3‐bis(chloromethyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The Dreiding 2.21 force field described by Mayo et al [37] and implemented in Cerius 2 OFF module was applied since it was found to be very suitable and reliable for the molecular simulation of aromatic polymers in accordance with previous studies [37][38][39][40][41][42]. This force field is parametized for a large class of organic molecules involving H, C, O, S, P, F, Cl and Br, allowing it to be applied to bio-and synthetic polymers [35][36][37][38][39][40][41][42]. It was found that the Dreiding 2.21 force field leads to accurate geometries for various polymeric systems and can be used to calculate and minimise the energy of a simulated polymeric system.…”
Section: Computational Methodologymentioning
confidence: 95%
See 2 more Smart Citations
“…The Dreiding 2.21 force field described by Mayo et al [37] and implemented in Cerius 2 OFF module was applied since it was found to be very suitable and reliable for the molecular simulation of aromatic polymers in accordance with previous studies [37][38][39][40][41][42]. This force field is parametized for a large class of organic molecules involving H, C, O, S, P, F, Cl and Br, allowing it to be applied to bio-and synthetic polymers [35][36][37][38][39][40][41][42]. It was found that the Dreiding 2.21 force field leads to accurate geometries for various polymeric systems and can be used to calculate and minimise the energy of a simulated polymeric system.…”
Section: Computational Methodologymentioning
confidence: 95%
“…The non-canonical 'T-damping' thermostat described by Berendsen et al [46,47] was used for isothermal-isobaric NPT-MD simulations. Molecular dynamics studies [25][26][27][28][29][30][31][32][37][38][39][40][41][42][43] have proven to provide a better insight into the physical phenomena exhibited by polymers. In the case of polymers, this technique can actually be used to predict physical (density, diffusion, and free volume) properties of a polymeric system.…”
Section: Computational Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…For a better understanding of this behavior, theoretical conformational analyses were e®ectuated. In our previous studies, the molecular modeling was very helpful in explaining the speci¯c degradation phenomena [8,12,13] or supra-molecular behavior [14,15,16,17]. If the polar surface is less than 5-5.5%, these studies indicate that the degradation process is not a®ected by the chain polarity [12,13].…”
Section: Resultsmentioning
confidence: 97%
“…In fact, an important goal in the synthesis of LCP is to design molecules with the necessary order to form a mesophase yet with sufficient chain flexibility so that the crystal melting temperature (T m ) is reached within the range of normal processing temperatures. Due to their unique physical properties like high strength and modulus, good thermal endurance, small linear expansion coefficient (comparable with ceramics), high chemical resistance, significant attention has been devoted to these materials [9][10][11][12][13][14][15]. One of the distinguishing structural properties of these polymers is the ease in producing a uniform molecular orientation [16][17].…”
Section: Introductionmentioning
confidence: 99%